Peran Partai Aceh (PA) dalam Mendorong Partisipasi Politik Masyarakat Aceh - Mansur Syakban; Sri Yunanto; Usni Usni (Pusat Riset dan Inovasi Nasional, 2025)
The presence of local parties, one of which is the Aceh Party (PA) in Aceh, is a form of democracy for strategic groups that have been at odds with the government, so its emergence can be one of the factors encouraging the people of Aceh to take part or participate in politics. The purpose of this research is to find out the role of the Aceh Party (PA) in encouraging the political participation of the Acehnese people and to find out the obstacles and challenges of the Aceh Party (PA) in encouraging the political participation of the people in Aceh.The theory used in this study is the theory of G. A. Almond. The research method used in this study is a qualitative research method. It is an approach that explores and understands the meaning that a number of individuals or groups of people consider to be derived from social and humanitarian problems. The data collection techniques used in the study were in-depth interviews and documentation. Data analysis techniques are carried out by content analysis, synthesis analysis and critical analysis. The results of the research on the Role of the Aceh Party (PA) in Encouraging Political Participation of the Acehnese Community, based on the results of the research show that the Aceh Party has made several efforts to improve the quality and their role in providing political education in Aceh, this is shown by the existence of activity programs to improve the quality of Aceh Party's internal human resources and the community in order to realize good political education in districts/cities throughout Aceh. Obstacles and Challenges of the Aceh Party (PA) in Encouraging Community Political Participation in Aceh, based on the results of the study, the main inhibiting factor for the Aceh Party in carrying out its duties is related to access to gampongs that are difficult to travel due to long distances and difficult terrain. The Indonesian government must be open in dealing with any problems that arise throughout Indonesia. It is hoped that local political parties must be able to improve the quality of their members and cadres so that they can really carry out their performance well and can really become a means of channeling people's aspirations. So there needs to be good cooperation between local political parties and the community.